The mediating role of Place Brand Image in the relationship between place branding communication strategies and Foreign Direct Investment - ALANSAARI, MOHAMED EISA (2022)
The main aim of this study was to identify and examine the mediating role of place brand image in the relationship between place brand communication strategies and FDI attraction. This quantitative study intended to bridge the gap of research regarding the relationship between place brand image, place branding and FDI attraction. In this regard, this thesis will explore how place branding, place brand image impacts the attraction of FDI. The study develops a novel model to understand the relationship between the concepts. Using the investment path development paradigm (IDP) as a starting point for this study. The thesis will specifically look into the five factors classified as to having an effect on FDI attraction: cost factors, market factors, infrastructure and technological factors, political and legal factors, social and cultural factors and examine how they relate to place branding and place brand image. Noting that the IDP model does not incorporate ‘soft factors’ in the model specifically place brand image this thesis incorporated the theories of corporate branding which developed a place brand communication model that includes three types of place brand communication strategies which effect place brand image and utilised the place brand image scale of past research to understand the relationship of the concepts. This holistic approach is seen to be highly rewarding in having a stronger view on FDI attraction factors and has not been applied by scholars before. One of the main anticipated contributions to knowledge is that it verify that place brand image is an important factor that needs to be incorporated in the FDI attraction model. This study is of importance because it makes several contributions to the place branding literature. First, it will provide significant data on the impact of place brand communication strategies on a place brand image. Moreover, undertaking the research will enable governments to adopt various policies and strategies aimed at creating a positive place brand and ultimately enable countries to understand the dimension and scope of place branding and its relationship to attracting foreign direct investments. Thus, the research will provide a theoretical and practical guide to the best practices place branding communication strategies in a cities’s context. Looking at the past studies in the area, it can be seen that this kind of research is lacking.